Sustainability of the Effects and Impacts of Using Digital Technology to Extend Maternal Health Services to Rural and Hard-to-Reach Populations: Experience From Southwest Nigeria - Akeju, David; Okusanya, Babasola; Okunade, Kehinde; Ajepe, Adegbenga; Allsop, Matthew J.; Ebenso, Bassey (Frontiers in Global Women's Health, 2022)
Background: Nigeria has one of the worst health and development profile globally. A weak health system, poor infrastructure and varied socio-cultural factors are cited as inhibitors to optimal health system performance and improved maternal and child health status. eHealth has become a major solution to closing these gaps in health care delivery in low- and middle-income countries (LMICs). This paper reports the use of satellite communication (SatCom) technology and existing 3G mobile network for providing video training (VTR) for health workers and improving digitization of healthcare data. Objective: To evaluate whether the expected project outcomes that were achieved at end-line evaluation of 2019, were sustained 12 months after the project ended. Methods: From March 2017 to March 2019, digital innovations including VTR and data digitization interventions were delivered in 62 healthcare facilities in Ondo State, southwest Nigeria, most of which lacked access to 3G mobile network. Data collection for the evaluation combined documents review with quantitative data extracted from health facility registers, and 24 most significant change stories to assess the longevity of outcomes and impacts of digital innovation in four domains of healthcare: use of eHealth technology for data management, utilization of health facilities by patients, standard of care, and staff attitude. Stories of most significant changes were audio-recorded, transcribed for analysis and categorised by the above domains to identify the most significant changes 12 months after project closedown. Results: Findings showed that four project outcomes which were achieved at end-line evaluation were sustained 12 months after project closedown namely: staff motivation and satisfaction; increased staff confidence to perform healthcare roles; improved standard of healthcare delivery; and increased adoption of eHealth innovations beyond health sector. Conversely, an outcome that was reversed following discontinuation of SatCom from health facilities is availability of accurate and reliable data for decision-making. Conclusion: Digital technology can have lasting impacts on health workers, patients and the health system, through improving data management for decision-making, standard of maternity service delivery, boosting attendance at health facilities and utilization of services. Locally driven investment is essential for ensuring long-term survival of eHealth projects to achieve SDGs in LMICs.